2022
DOI: 10.1101/2022.01.23.22269719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Should healthcare workers with SARS-CoV-2 household exposures work? A Cohort Study

Abstract: Due to high community transmission of the Omicron variant, healthcare workers (HCWs) have been increasingly reporting household exposures to confirmed COVID19 cases. Quebec (Canada) provincial guidelines required to quarantine these HCWs. Facing the risk of staffing shortages, our hospital decided to allow them to work. Objective: To evaluate the risk for HCWs, who were household contacts, to become positive for COVID19 and evaluate the risk of nosocomial COVID19 transmission. Design: Cohort of consecutive H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although there are not many studies on this subject, the rate of asymptomatic Omicron infections is estimated to be between 25-54%. In a study conducted on healthcare workers, the rate of asymptomatic patients was found to be 50% in patients infected with the Omicron variant (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are not many studies on this subject, the rate of asymptomatic Omicron infections is estimated to be between 25-54%. In a study conducted on healthcare workers, the rate of asymptomatic patients was found to be 50% in patients infected with the Omicron variant (18).…”
Section: Discussionmentioning
confidence: 99%